Influence of red wine polysaccharides on cytochrome P450 enzymes and inflammatory parameters in tumor models - Stipp, Maria Carolina; Kulik, Juliana Danna; Corso, Claudia Rita; Galindo, Claudia Martins; Adami, Eliana Rezende; Evangelista, Alberto Gonçalves; Luciano, Fernando Bittencourt; Winnischofer, Sheila Maria Brochado; Cadena, Silvia Maria Suter Correia; Sassaki, Guilherme Lanzi; Acco, Alexandra (International journal of biological macromolecules, 2023)
The soluble fraction of polysaccharides from cabernet franc red wine (SFP) previously showed antitumoral effects by modulating the immune system. The present study tested the hypothesis that the SFP can regulate CYPs in vitro in HepG2 cells and in vivo in Walker-256 tumor-bearing rats. The SFP was used in the following protocols: (i) solid tumor, (ii) liquid tumor, and (iii) chemopreventive solid tumor. The SFP reduced solid tumor growth in both solid tumor protocols but did not inhibit liquid tumor development. The SFP reduced total CYP levels in the solid and liquid tumor protocols and reduced the gene expression of Cyp1a1 and Cyp2e1 in rats and CYP1A2 in HepG2 cells. An increase of N-acetylglucosaminidase activity was observed in all SFP-treated rats, and TNF-α levels increased in the solid tumor protocol in the vehicle, SFP, and vincristine (positive control) groups. The chemopreventive solid tumor protocol did not modify CYP levels in the liver or intestine or N-acetylglucosaminidase and myeloperoxidase activity in the liver. The in vitro digestion and nuclear magnetic resonance analyses suggested that SFP was minimally modified in the gastrointestinal system. In conclusion, SFP inhibited CYPs both in vivo and in vitro, likely as a result of its immunoinflammatory actions. [Display omitted] •The soluble fraction of polysaccharides from cabernet franc red wine (SFP) had antineoplastic effect against Walker-256 solid tumor.•SFP had antitumoral effect in treatment and chemoprentive protocols.•SFP did not inhibit liquid Walker-256 tumor development in rats.•SFP inhibited CYPs both in vivo and in vitro, likely as a result of its immunoinflammatory actions.•SFP was minimally modified in the in vitro digestion system.